Knowledge, attitude and practice of workers toward usage of the Personal Protective Equipment (PPE) / Nur’amirah Mohd Ismail - Mohd Ismail, Nur’amirah (2019)
The growing safety and health issue in oil palm mill employees has different impacts and management problems. One of the primary factors that trigger the issue is that the employees do not wear the correct Personal Protective Equipment (PPE) during their job. This research was performed to study the worker’s Knowledge, Attitude and Practice of using of PPE in oil palm mill undertaken by the management of the palm oil mill. The technique by distributing the questionnaire to the chosen palm oil mill in Perak in conducting this study. Data were collected from 30 participants from the Eng Thye Plantation Kuala Gula, Perak, using the questionnaire technique. The questionnaire was sent to the palm oil mill by manually spreading it to the respondent. All the information registered and analyses by using the Statistical package for Social Science (SPSS) consists of the descriptive analysis, correlation and multiple regression. The finding demonstrates that all the independent variable that is knowledge level of employees, attitude of the employees and practice of the employees toward the use of the PPE has the positive connection to the dependent variable. There is a significant connection between employees’ KAP toward use of the PPE. The finding also show relationship between employee attitudes that the most influential variable affects the use of PPE. The results can provide helpful data for a better comprehension of factor that can affect employees to use the PPE. Management of palm oil mill could use the finding to create a correct plan to enhance data and plan how to decrease the safety and health issue at the palm oil mill.